A new method for the deflection analysis of composite beams with periodically varying interfaces. Issue 5 (13th December 2017) - Li, Botong; Liu, Chein‐Shan
Abstract: For the deflection analysis of the composite beams with periodically varying interfaces and under different boundary conditions we develop new iterative methods by using integral equations through a weak‐form formulation, and using the sinusoidal functions as both the test functions and the bases of numerical solutions. Due to the orthogonality of sinusoidal functions and the use of the Drazin inversion formula, the closed‐form solutions of coefficients can be found out. As a consequence, the present iterative schemes demonstrate their quick convergence, which are useful tools to analyze the deflections for three popularly used composite beams. Abstract : For the deflection analysis of the composite beams with periodically varying interfaces and under different boundary conditions we develop new iterative methods by using integral equations through a weak‐form formulation, and using the sinusoidal functions as both the test functions and the bases of numerical solutions. Due to the orthogonality of sinusoidal functions and the use of the Drazin inversion formula, the closed‐form solutions of coefficients can be found out. As a consequence, the present iterative schemes demonstrate their quick convergence, which are useful tools to analyze the deflections for three popularly used composite beams.